2002
DOI: 10.1126/science.1067159
|View full text |Cite
|
Sign up to set email alerts
|

Complete Development of Mosquito Phases of the Malaria Parasite in Vitro

Abstract: Methods for reproducible in vitro development of the mosquito stages of malaria parasites to produce infective sporozoites have been elusive for over 40 years. We have cultured gametocytes of Plasmodium berghei through to infectious sporozoites with efficiencies similar to those recorded in vivo and without the need for salivary gland invasion. Oocysts developed extracellularly in a system whose essential elements include co-cultured Drosophila S2 cells, basement membrane matrix, and insect tissue culture medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 27 publications
3
69
0
5
Order By: Relevance
“…It has been known for several decades that parasites injected into the haemocoel can develop further upon binding onto the mosquito midgut wall (Weathersby, 1952;Warburg and Schneider, 1993), and this was confirmed in a dramatic way when it was shown that the injection of parasites into Drosophila melanogaster also leads to the development of infective sporozoites within oocysts attached to the basal lamina at multiple sites, not just the midgut (Schneider and Shahabuddin, 2000). Thus, binding of the ookinete to the basal lamina is a condition that supports its development into a functional oocyst, as demonstrated with the critical requirement of Matrigel in the successful culture of Plasmodium berghei in vitro (Al-Olayan et al, 2002).…”
mentioning
confidence: 67%
“…It has been known for several decades that parasites injected into the haemocoel can develop further upon binding onto the mosquito midgut wall (Weathersby, 1952;Warburg and Schneider, 1993), and this was confirmed in a dramatic way when it was shown that the injection of parasites into Drosophila melanogaster also leads to the development of infective sporozoites within oocysts attached to the basal lamina at multiple sites, not just the midgut (Schneider and Shahabuddin, 2000). Thus, binding of the ookinete to the basal lamina is a condition that supports its development into a functional oocyst, as demonstrated with the critical requirement of Matrigel in the successful culture of Plasmodium berghei in vitro (Al-Olayan et al, 2002).…”
mentioning
confidence: 67%
“…Until recently, in vitro differentiation of P. berghei was limited to the ookinete stages (12). Recently, progress has been made toward developing procedures for in vitro differentiation to later stages (22,23), but these are not readily amenable for large-scale cultures. To circumvent some of these limitations we used subtractive hybridization, by which cDNAs from non-infected midguts were subtracted from cDNAs from infected midguts.…”
Section: Discussionmentioning
confidence: 99%
“…Ookinetes are elongated, motile cells that penetrate the chitin-containing peritrophic matrix using chitinases and proteases, 9,10 invade and cross midgut epithelial cells, and finally, come to rest and develop into oocysts at the basal lamina. 11 Within oocysts, sporozoites develop by asexual reproduction and fission, eventually releasing thousands of sporozoites that make their way to salivary glands, ready to be injected into new vertebrate hosts during blood meal ingestion.…”
Section: Introductionmentioning
confidence: 99%